Issues of Good Agriculture Practice in Market Access - Perspectives of the Traders in the Development of the Papaya Industry - Chan, K.
This paper attempts to illustrate the challenges of market access for tropical fruit producing countries that are looking at export-led growth approaches to the development of their tropical fruit industry. The case for the papaya industry is quoted. The paper examines the guiding principles of Good Agriculture Practice, GAP, and how these principles could be a useful tool in overcoming the problems of market access. Papaya growers are finding it more and more difficult to manage their pest and disease problems. Many resort to more frequent pesticide application and more toxic pesticides. The issue of MRL becomes prominent. Transnational supermarkets are getting more powerful and more stringent with their product quality definition. Importing countries are enacting very convincing and effective NTB on the papaya producing countries, as quickly as they are signing Free Trade Agreements with the same producer countries. The farmers are faced with a multitude of dead-ends. Where do they go from here? Good Agriculture Practice could be an approach towards overcoming many of the problems faced by the farmers; (i)by complying with the requirements of the supermarket buyers, and (ii)with better cultivation practices and the knowledge that the farmers could derive from the researchers, the farmers could achieve more sustainable production. However, these could only remain as illusive policy objectives for many governments of the producer countries. There is much that the government has to do to in order to realize these aims; ensuring an effective transfer of knowledge and technology to the farmers, that there are capable extension officers to do the work, that the infrastructure capacities are in place, and that all the stakeholders of the industry fully understand what GAP is really about.
Keywords: GOOD AGRICULTURE PRACTICE; FOOD SAFETY; SUSTAINABLE PRODUCTION; MARKET ACCESS; TRANSFER OF TECHNOLOGY; CONSUMER CONFIDENCE